2022
DOI: 10.3389/fonc.2022.1057198
|View full text |Cite
|
Sign up to set email alerts
|

NUF2 overexpression contributes to epithelial ovarian cancer progression via ERBB3-mediated PI3K-AKT and MAPK signaling axes

Abstract: IntroductionNDC80 kinetochore complex component (NUF2) is upregulated and plays an important role in various human cancers. However, the function and mechanism of NUF2 in epithelial ovarian cancer (EOC) remain unclear.MethodsNUF2 expression was detected in EOC tissues and cell lines. The effects of NUF2 downregulation on cell proliferation, migration and invasion in EOC were analyzed by CCK-8 and Transwell assays. Meanwhile, the effect of NUF2 downregulation on tumor growth in vivo was determined by xenograft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have indicated that NUF2 can regulate ERBB3 expression in the context of epithelial ovarian cancer progression via the PI3K-AKT and MAPK signaling axes [12] . However, the specific mechanism by which NUF2 regulates ERBB3 expression has not been extensively investigated in HCC.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that NUF2 can regulate ERBB3 expression in the context of epithelial ovarian cancer progression via the PI3K-AKT and MAPK signaling axes [12] . However, the specific mechanism by which NUF2 regulates ERBB3 expression has not been extensively investigated in HCC.…”
Section: Resultsmentioning
confidence: 99%
“…KIRP, the second most prevalent subtype of renal cell carcinoma, is usually detected incidentally during routine physical examinations [ 30 ]. Recently, a substantial body of evidence has suggested that CDCA genes are correlated with cancer occurrence, progression, and prognosis [ 8 , 16 ]. However, there are currently few studies on their roles in KIRP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that any disorder in cell division can lead to cancer onset and progression [ 6 , 7 ]. Furthermore, previous reports have suggested that the aberrant expression of CDCAs is strongly correlated with some human cancers, including ovarian cancer [ 8 ], hepatocellular carcinoma [ 9 ], prostate cancer [ 10 ], nasopharyngeal carcinoma [ 11 ], breast cancer [ 12 ], pancreatic adenocarcinoma [ 13 ], stomach carcinoma [ 14 ], hypopharyngeal squamous cell carcinoma [ 15 ], and non-small cell lung cancer [ 16 ]. Notably, few studies have described the relationship between certain members of the CDCA family and the immune microenvironment.…”
Section: Introductionmentioning
confidence: 99%